Acute hepatitis C virus (HCV) infection in chronic carriers of hepatitis B virus (HBV): the impact of underlying active HBV replication on persistence of HCV infection and antibody responses to HCV. (1st July 2002) - Chu, C-M; Yeh, C T; Sheen, I S; Liaw, Y F
Abstract : Background and aims: The aim of this study was to assess whether underlying chronic hepatitis B virus (HBV) infection interferes with persistence of hepatitis C virus (HCV) infection and humoral immune responses to HCV in acute HCV infection. Methods: Serial sera from 12 patients with acute HCV infection (group A) and 12 hepatitis B surface antigen (HBsAg) carriers with acute HCV infection (seven anti-hepatitis B e antigen (anti-HBe) positive (group B1) and five hepatitis B e antigen (HBeAg) positive (group B2)) were tested for HCV RNA by polymerase chain reaction, and anti-HCV by third generation enzyme immunoassay and confirmatory assay. Serial serum samples from HBsAg carriers were also tested for HBeAg, anti-HBe, and HBV DNA by hybridisation assay. Results: Persistent HCV viraemia for more than six months was significantly more frequent in groups A (83%) and B1 (86%) than in group B2 (0%). Anti-HCV was detected in 100% and 86% of group A and group B1 one month after onset while only one group B2 patient was transiently anti-HCV positive 1–2 months after onset. Of the latter, three had anti-core 1 less than two months after onset while no patient responded to other HCV antigens. Overall, of six HBsAg carriers with acute self limiting HCV infection, only one had transient anti-HCV and three had transient anti-core 1. HBV DNA became undetectable transiently in four and persistently in one group B2 patient. Conclusion: The presence of active HBV replication can inhibit the persistence of HCV infection and antibody responses to HCV. Acute HCV infection in HBsAg carriers with active HBV replication usually presents transient HCV viraemia with poor antibody responses to HCV.